2004
DOI: 10.1152/ajpheart.00791.2003
|View full text |Cite
|
Sign up to set email alerts
|

NO and endogenous angiotensin II interact in the generation of renal sympathetic nerve activity in conscious rats

Abstract: Nitric oxide (NO) appears to inhibit sympathetic tone in anesthetized rats. However, whether NO tonically inhibits sympathetic outflow, or whether endogenous angiotensin II (ANG II) promotes NO-mediated sympathoinhibition in conscious rats is unknown. To address these questions, we determined the effects of NO synthase (NOS) inhibition on renal sympathetic nerve activity (RSNA) and heart rate (HR) in conscious, unrestrained rats on normal (NS), high-(HS), and low-sodium (LS) diets, in the presence and absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The fact that we observed a reduced pressor response to L-NAME under control conditions suggests that the peripheral downregulation of NOS or decreases in NO vascular sensitivity, or both, contribute more to the cardiovascular response to systemic L-NAME than central upregulation of NOS. It is possible that the short time course during which we examined NOS inhibition (10 min) did not allow for full blockade of NOS in the brain, because a longer time course appears to be required for central NOS inhibition after systemic administration of NO inhibitors (24,37,61). Clearly, further studies are required to assess the actions of increased neural NO and its role in cardiovascular alterations produced by hindlimb unloading (43,62).…”
Section: Ajp-regul Integr Comp Physiolmentioning
confidence: 99%
“…The fact that we observed a reduced pressor response to L-NAME under control conditions suggests that the peripheral downregulation of NOS or decreases in NO vascular sensitivity, or both, contribute more to the cardiovascular response to systemic L-NAME than central upregulation of NOS. It is possible that the short time course during which we examined NOS inhibition (10 min) did not allow for full blockade of NOS in the brain, because a longer time course appears to be required for central NOS inhibition after systemic administration of NO inhibitors (24,37,61). Clearly, further studies are required to assess the actions of increased neural NO and its role in cardiovascular alterations produced by hindlimb unloading (43,62).…”
Section: Ajp-regul Integr Comp Physiolmentioning
confidence: 99%
“…Therefore, we tested the hypothesis that during pregnancy NO contributes to impaired baroreflex gain by determining, first, whether acute systemic blockade of the NOS enzyme increases the gain of the baroreflex control of heart rate in conscious pregnant rabbits. We also determined whether the mRNA and protein levels of nNOS in the NTS, RVLM, CVLM, and PVN were altered in pregnant compared with nonpregnant rabbits.Recent studies suggest that the actions of NO in setting basal sympathetic tone and baroreflex control depend on an interaction with angiotensin II (28,30,33,36,45). For example, Kumagai et al (28) found that, in spontaneously hypertensive rats, blockade of either angiotensin II AT 1 receptors or the NOS enzyme alone increased the gain of baroreflex control of heart rate and renal sympathetic nerve activity.…”
mentioning
confidence: 99%
“…Recent studies suggest that the actions of NO in setting basal sympathetic tone and baroreflex control depend on an interaction with angiotensin II (28,30,33,36,45). For example, Kumagai et al (28) found that, in spontaneously hypertensive rats, blockade of either angiotensin II AT 1 receptors or the NOS enzyme alone increased the gain of baroreflex control of heart rate and renal sympathetic nerve activity.…”
mentioning
confidence: 99%
“…These responses have been reproduced in conscious rats, where microinjection of SNP into the RVLM increased arterial pressure (16). Finally, in conscious rats, intravenous infusion of L-NAME, combined with infusion of hydralazine to maintain baseline levels of blood pressure, caused profound inhibition of RSNA and bradycardia, suggesting a sympathoexcitatory role for NO (22).…”
Section: Discussionmentioning
confidence: 78%